Compensating Unsecured Creditors for Extraordinary Bankruptcy Reorganization Risks - Lynn M. LoPucki; William C. Whitford (Washington University Law Quarterly, 1994)
To reduce creditors' and shareholders' incentives to resist managers' efforts to maximize, we proposed that parties to the reorganization case who stand to benefit during the pendency of a Chapter 11 reorganization from a particular investment be required to compensate those disadvantaged by it. The purpose of this article is to elaborate on that proposal.
Keywords: Bankruptcy reorganization; Debtor and creditor; United States; Investments; Corporate governance